Boosting the thermal efficiency of a flat-tube parabolic trough solar collector with the introduction of innovative slashed triangular prism turbulators - Sultan Alshehery; Qasem Al Mdallal; Ahmed A. Altohamy; Lotfi Ben Said; Mohamed Bouzidi; Turki Alkathiri; Lioua Kolsi (Case Studies in Thermal Engineering)
This study focuses on enhancing the thermal performance of parabolic trough solar collectors (PTSC) by modifying the geometry of the absorber tube to a flat design. For the first time, an innovative turbulator known as the triangular prisms turbulator (TPT) has been utilized, with its geometry specifically designed to fit precisely within the flat tube. Tests were conducted on various geometric parameters, including turbulator lengths (l) of 5–20 mm, slash areas (A) ranging from 4 to 40 mm2, and clearance (C) from 0.25 to 1 mm. Results show that the flat tube design achieves a 28 % higher performance enhancement coefficient (PEC) than the circular tube. Utilizing TPT with varying lengths revealed that the l = 15 mm configuration produced a pressure drop of 18.3 times and enhanced heat transfer by 525 %, yielding a PEC of 2.37, thereby outperforming all other lengths tested. In addition, incorporating slashes on the TPT caused PEC to increase to 3.32 at a slash area of 33 mm2, even though there was a notable decline in heat transfer and pressure drop. Ultimately, the alteration of the clearance between the turbulator and the tube wall facilitated the selection of 0.75 mm as the most optimal design. This adjustment resulted in a pressure drop and heat transfer enhancement of 360 % and 464 %, respectively, yielding the highest PEC of 3.37 documented in this study.